The diagnosis and determine the level of balance between the time available for life and work: The case study of a sample of doctors hospitals City of Medicine - حمود سعد علي; عيسى مصطفى جعفر (Journal of Economics and Administrative Sciences, 2017)
Purpose: The diagnosis and determine the level of balance between the time available for life and work with the doctors in the hospitals of t the six hospitals in the City of Medicine. Design / methodology / Approach: It has been relying on ready-scale, to make sure the diagnosis and determine the level of balance between the time available for life and work, where they were distributed on Form 42 doctors in the six hospitals in the City of Medicine, were analyzed by software (Nvivo and SPSS v.22). Results: The results showed that there is a good level of balance between the time available for life and work with the doctors. Research limitations: The difficulty of distributing and collecting the forms for doctors in hospitals and clinics, emerging as a result of the continuing busy the doctors work assigned to them. Practical implications: You can benefit from the findings of the researcher, in the interest and to strengthen the balance between the time available for life and work, can help to improve the performance of hospitals in the City of Medicine.